Changes in Men's Knowledge & Attitudes Following Health Education on their Role in Preventing Maternal Deaths: An Exploratory Survey in a Nigerian Community - Omokhoa Adedayo Adeleye; Chukwunwendu Anthony Okonkwo (Social Medicine Publication Group, 2016)
Background: In developing countries, men are sometimes stereotypically perceived as uninterested in maternal health, but their reproductive health roles have been widely recognized. Some studies have suggested that effective communication with men on safe motherhood can yield behavior changes capable of reducing maternal deaths. Aim: This study's objective was to study the impact of an educational session on the knowledge and attitudes of married men regarding maternal deaths. Design: Men were interviewed before the intervention and then participated in a joint educational session on safe motherhood. Follow-up interviews took place three months after the intervention. Results: 141 randomly selected men enrolled in the study; 122 completed both interviews. After the session, men were more likely to recognize a danger sign of pregnancy and delivery, but there was no increase in their willingness to participate in making the local hospital better for maternal healthcare. Mean composite scores increased significantly. Conclusions: Married men have moderate knowledge about maternal deaths and are potentially educable regarding their prevention. Further controlled intervention programs and studies are recommended.